Cognitive Improvement After Kidney Transplantation Is Associated With Structural and Functional Changes on MRI. Issue 3 (March 2020) - van Sandwijk, Marit S.; ten Berge, Ineke J. M.; Caan, Matthan W. A.; Düring, Marco; van Gool, Willem A.; Majoie, Charles B. L. M.; Mutsaerts, Henk-Jan M. M.; Schmand, Ben A.; Schrantee, Anouk; de Sonneville, Leo M. J.; Bemelman, Frederike J.
Abstract : Background: Several studies have reported improved cognitive outcomes after kidney transplantation, but most studies either did not include controls or lacked extensive neuroimaging. In addition, there is uncertainty whether kidney donation is a safe procedure in terms of cognitive outcomes. Methods: We prospectively studied neurocognitive function in kidney transplant recipients. The primary outcome was change in neurocognitive function after 1 year compared with baseline, which was evaluated using the Amsterdam Neuropsychological Task battery and verbal fluency tests. Secondary outcomes included changes in depression and anxiety (measured by the Hospital Anxiety and Depression scale) and changes in fatigue (measured by the Checklist for Individual Strength). We included kidney donors to control for learning effects, socioeconomic status, and surgery. In addition, kidney transplant recipients were evaluated with MRI scans at baseline and at year 1. The MRI protocol included conventional MRI, automated volumetric measurement, diffusion tensor imaging, magnetic resonance spectroscopy, arterial spin labeling, and a resting state functional MRI. Results: Twenty-seven recipients and 24 donors were included. For both recipients and donors, neuropsychologic testing scores improved 1 year after transplantation (donation). Recipient improvement significantly exceeded donor improvement on tasks measuring attention and working memory. These improvements were associated with increases in white matter volume and N -acetylaspartate/creatine (a marker for neuronal integrity). Conclusions: Attention and working memory improve significantly 1 year after kidney transplantation. Learning effects do not account for these improvements because recipient improvement in these areas exceeds donor improvement and correlates with an improvement in white matter integrity after transplantation. Kidney donation appears to be a safe procedure in terms of cognitive outcomes. Abstract : Supplemental Digital Content is available in the text.